25 0H Vitamin D Levels in Pregnant Females: The Hidden Time Bomb - Zuhra, Fatima Tuz; Mehnaz; Atzaz, Noreen; Shabana; Iqbal, Asma; Saeed, Sami (Journal of Rawalpindi Medical College, 2023)
Objective: To assess and correlate changes in vitamin D levels in three trimesters of pregnancy. Material and methods: This longitudinal study was conducted in collaboration with the Gynecology & Obstetric and Pathology department of Fauji foundation hospital, Rawalpindi. Eighty pregnant females were included in the study and tested for vitamin D at three points of time i.e. first trimester gestational age: (7-13 weeks), second trimester (20-26weeks), and third trimester (33 weeks till term). Pregnant females at their first visit and healthy nonpregnant females (controls) were analyzed for vitamin D, vitamin B12, folate, ferritin, and Hemoglobin (Hb) levels and compared using the Mann- Whitney U test for vitamin D and independent sample t-test for other parameters. Vitamin D and Hemoglobin (Hb) testing was done during the first, second, and third trimesters among pregnant females and compared between three groups using the Kruskal Wallis test and paired t-test respectively. Results: Mean age of the pregnant females was 35 years. Mean vitamin D levels showed a significant decline from 30.7 ng/ml vs 19.5 ng/ml vs 18.6 ng/ml for the first, second, and third trimesters respectively (p-value<0.05). The frequency of vitamin D deficiency was 15.1% for pregnant females at their first visit which progressed to 20% and 25% in the second and third trimesters respectively. Conclusion: Increased vitamin D deficiency and insufficiency rates exist in pregnant females, which progresses to further decline in the ensuing trimesters.